A high-flow nasal cannula system with relatively low flow effectively washes out CO2 from the anatomical dead space in a sophisticated respiratory model made by a 3D printer - Yu Onodera; Ryo Akimoto; Hiroto Suzuki; Masayuki Okada; Masaki Nakane; Kaneyuki Kawamae (Intensive Care Medicine Experimental, 2018)
Abstract Background Although clinical studies of the high-flow nasal cannula (HFNC) and its effect on positive end-expiratory pressure (PEEP) have been done, the washout effect has not been well evaluated. Therefore, we made an experimental respiratory model to evaluate the respiratory physiological effect of HFNC. Methods An airway model was made by a 3D printer using the craniocervical 3D-CT data of a healthy 32-year-old male. CO2 was infused into four respiratory lung models (normal-lung, open- and closed-mouth models; restrictive- and obstructive-lung, open-mouth models) to maintain the partial pressure of end-tidal CO2 (PETCO2) at 40 mmHg. HFNC flow was changed from 10 to 60 L/min. Capnograms were recorded at the upper pharynx, oral cavity, subglottic, and inlet sites of each lung model. Results With the normal-lung, open-mouth model, 10 L/min of HFNC flow decreased the subglottic PETCO2 to 30 mmHg. Increasing the HFNC flow did not further decrease the subglottic PETCO2. With the normal-lung, closed-mouth model, HFNC flow of 40 L/min was required to decrease the PETCO2 at all sites. Subglottic PETCO2 reached 30 mmHg with an HFNC flow of 60 L/min. In the obstructive-lung, open-mouth model, PETCO2 at all sites had the same trend as in the normal-lung, open-mouth model. In the restrictive-lung, open-mouth model, 20 L/min of HFNC flow decreased the subglottic PETCO2 to 25 mmHg, and it did not decrease further. As HFNC flow was increased, PEEP up to 7 cmH2O was gradually generated in the open-mouth models and up to 17 cmH2O in the normal-lung, closed-mouth model. Conclusions The washout effect of the HFNC was effective with relatively low flow in the open-mouth models. The closed-mouth model needed more flow to generate a washout effect. Therefore, HFNC flow should be considered based on the need for the washout effect or PEEP.